Psycholinguistic-Based Digital Interactive Storytelling for Strengthening Literary Literacy and Pancasila Values - Herinto Sidik Iriansyah; Purwani Puji Utami; Maria Ulfa (LPPM STKIP Kusuma Negara, 2026)
The transformation of 21st-century education requires literacy learning that improves reading competence while strengthening character and national values. Although digital storytelling has been widely used to support literacy development, a few studies have integrated psycholinguistic principles with digital interactive storytelling to simultaneously enhance literary literacy and Pancasila values among elementary school students. This study investigated the effectiveness of psycholinguistic-based digital interactive storytelling in improving literary literacy and strengthening Pancasila values among sixth-grade students at SDN Klender 03, East Jakarta. This classroom action research employed the Kemmis and McTaggart model in two cycles involving 31 students. Data were collected through literary literacy tests, observation sheets, interviews, and documentation. Literary literacy indicators included identifying story elements, interpreting meaning, drawing conclusions, and evaluating literary texts, while Pancasila values included cooperation, responsibility, empathy, critical thinking, and respect for diversity. The mean literary literacy score increased from 64.8 in the baseline condition to 74.2 in Cycle I and 84.6 in Cycle II, while learning mastery improved from 43.3% to 90%. Observation results also indicated improvements in Pancasila value indicators. These findings suggest that psycholinguistic-based digital interactive storytelling effectively enchances literary literacy and Pancasila values in elementary education.